2011
DOI: 10.1007/s12257-011-0278-1
|View full text |Cite
|
Sign up to set email alerts
|

Fermentation of seaweed sugars by Lactobacillus species and the potential of seaweed as a biomass feedstock

Abstract: It is known that seaweeds differ greatly from land plants in their sugar composition. The current research on the L-lactic acid fermentation process focuses on land plant sugars as a carbon source, with the potential of seaweed sugars being largely ignored. This study examined the feasibility of seaweed biomass as a possible carbon source for the production of L-lactic acid, by comparing the fermentation of seaweed sugars (D-galactose, D-mannitol, L-rhamnose, D-glucuronic acid, and L-fucose) and land plant sug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(20 citation statements)
references
References 27 publications
2
17
0
1
Order By: Relevance
“…Despite the low mannitol concentration, the fermentation process advanced successfully, presumably on the basis of the dextrose used as carrier in the LAB starter culture, the concentration of which was up to 18 times as high as the natural concentration of mannitol from the seaweed. Regardless of the low absolute level of mannitol detected, the almost total absence of mannitol in the fermented biomass, indicated that either the mannitol was drained to the liquid fraction of the fermentation (Herrmann et al 2015) or consumed by the LAB in the fermentation process, as previously described (Black 1955;McDonald et al 1991;Hwang et al 2011). The content of WSC (dextrose + mannitol) in this study was in the same range as in Herrmann et al (2015): 256 g kg −1 TS, as compared to 217 g kg −1 TS.…”
Section: Discussionmentioning
confidence: 57%
“…Despite the low mannitol concentration, the fermentation process advanced successfully, presumably on the basis of the dextrose used as carrier in the LAB starter culture, the concentration of which was up to 18 times as high as the natural concentration of mannitol from the seaweed. Regardless of the low absolute level of mannitol detected, the almost total absence of mannitol in the fermented biomass, indicated that either the mannitol was drained to the liquid fraction of the fermentation (Herrmann et al 2015) or consumed by the LAB in the fermentation process, as previously described (Black 1955;McDonald et al 1991;Hwang et al 2011). The content of WSC (dextrose + mannitol) in this study was in the same range as in Herrmann et al (2015): 256 g kg −1 TS, as compared to 217 g kg −1 TS.…”
Section: Discussionmentioning
confidence: 57%
“…Recently, we established the metabolic pathway of 3,6-anhydro-Lgalactose [33], which is one of the main sugar components in Gracilaria, and this would further improve the bioethanol productivity of red seaweeds. Our analysis also indicates U. pertusa would be less useful for the production of L-lactic acid [34,35], whose degree of reductance is 4.0, due to its low degree of reductance compared to other biomass feedstocks. However, U. pertusa would be a fine feedstock for the production of acid products, such as D-glucaric acid (γ = 3.00) and succinic acid (γ = 3.50).…”
Section: Degree Of Reductance Of U Pertusamentioning
confidence: 82%
“…To date, marine algae have been used in the production of bio-based chemicals [37,38] and biofuels [39,40], which is an indication of their great potential as carbon sources for lactic acid fermentation. In this study, we used lactic acid bacteria for the fermentation of the marine algae Gracilaria sp., Sargassum siliquosum, and Ulva lactuca for lactic acid production.…”
Section: Introductionmentioning
confidence: 99%